New Media and Peace Activism: the Case of “One Million Voices against FARC” (2014)
Recently, the spread of social media has undoubtedly contributed to further increasing the potential of civil society mobilizations. The ease of access to new communication technologies enhances the po- tential of civic movements, but it is still necessary to focus on the relationship between the creation and stability of digital ties and the sustainability of collective action. This article aims to examine the first and largest global civil mobilization promoted through a So- cial Network Site: the massive march on February 4th 2008 against the FARC, the Colombian guerrilla group. The objective is to analyze, several years after the fact, the characteristics and effects of this mo- bilization, which originated on the web to become a huge global march. Through the analysis of the literature it presents some reflections on the nature of these new forms of online activism, their potential and limits. Specifically, the case in question comprises a form of collective action that, while displaying impressive speed and the capacity to mobilize many people thanks to the new medium of communication, at the same time reveals its dependence on external actors with the ability to manipulate it for their own ends as well as its weakness in generating a thorough prospect for social change that can truly impact on Columbian society in the long run. In conclusion the present work shows that, in a complex environment characterized by high levels of conflict, the resources provided by ‘revolutionary’ new media are not sufficient to achieve concrete social change because the web, like a mirror, simply brings the same contradictions found in real space into a virtual space. Therefore, we suggest looking beyond the emotional impact produced by new media and more carefully analyzing the real dynamics of conflicts and the inevitable ‘imbrication’ of the digital and non-digital.